Understanding the context of distance students: Differences in on- and off-campus engagement with an online learning environment - Stuart Palmer (Flexible Learning Association of New Zealand, 2012)
While a growing number of higher education institutions are providing online modes of study for both on- and off-campus students, there are very real differences in demography, technology experiences, reasons for study, etc. between on- and off-campus students, and research into engagement with online learning environments (OLEs) indicate differences in the way that on- and off-campus students interact with OLEs.  In Australia, Deakin University is a major provider of distance and online education, and provides a case study of a higher education institution with a mature and large-scale OLE implementation providing support to both on- and off-campus students.  Deakin Studies Online (DSO) is Deakin University's OLE.  Based on a representative sample of 1322 responses to the 2011 DSO evaluation survey, this paper presents a large-scale, up-to-date and fine-grained investigation of impact of mode of study on the student experience of using an OLE.  It was found that the primary place of access to DSO for both groups was home, mobile access to DSO seems likely to be of growing importance to both groups, and there was no statistically significant difference in the mean satisfaction ratings between on- and off-campus students for virtually all DSO functions.  Off-campus students gave significantly higher mean ratings of importance (though not satisfaction) to a range of DSO functions that could be viewed as 'value adders' by off-campus students, enhancing their overall learning experience.  For more than half of the DSO functions surveyed, on-campus students reported statistically significant higher mean frequency of access than off-campus students.  The finding that elements of the institutional OLE are not universally perceived and used the same way by all students groups challenges the value of standard, one-size-fits-all institutional policies and templates relating to the use of OLEs.